Renal Abnormalities in Young Healthy Individuals on Screening Ultrasonography of Kidneys - Saqib, Rizwan; Bangash, Tajamul Hussain; Ahmed, Sajad; Asim Niaz, Muhammad Muttahhar; Sabir, Ghulam; Fatima, Sughra (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the prevalence of renal abnormalities in young healthy individuals on screening ultrasonography of kidneys.Study Design: Cross sectional studyPlace and Duration of Study: Combined Military Hospital, Hyderabad from Sep 2019 to Mar 2020.Methodology: 2050, Young asymptomatic healthy individuals of 15-24 years age, coming to radiology department for screening ultrasound of kidneys were included in the study. The examination was performed with standard convex probe of 3.5MHz on Aloka Pro sound SSD-3500 Ultrasound machine by experienced radiologist. Both kidneys were scanned with patient in supine and lateral positions. The images were taken in both longitudinal and transverse sections.Results: Out of 2050 cases included in the study, 112 (5.46 %) had renal abnormalities, 81 (3.95 %) had renal calculi, hydronephrosis was found in 14 (0.68%) cases, out of which ten were due to calculi, 9 (0.44%) individuals had abnormalities of size, shape and position and renal cysts were found in 7 (0.34%) cases with six simple and one septated cyst, while only 1 (0.05%) case had bilaterally echogenic kidneys.Conclusion: The overall prevalence of renal abnormalities was 5.46% with calculi comprising the major abnormality. Early detection with ultrasound screening can prevent further damage to the kidneys in young asymptomatic healthy individuals. It is recommended to perform screening ultrasonography of kidneys, ureters and bladder in young candidates before induction in services.